2004
DOI: 10.4219/jsge-2004-464
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Student Perceptions of Classroom Quality: Instrumentation and Differences Between Advanced/Honors and Nonhonors Classes

Abstract: This article describes the initial development and psychometric evaluation of an instrument for use with secondary students to measure various perceptions about class activities. The instrument-Student Perceptions of Classroom Quality (SPOCQ)-focuses on meaningfulness, challenge, choice, self-efficacy, and appeal, constructs central to learning and deeply rooted in gifted education. The article reports content and construct validity evidence, reliability estimates, and demographic group comparisons from a dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(100 citation statements)
references
References 17 publications
7
92
1
Order By: Relevance
“…Indeed, the American Association of University Women Annual Report (1992) concluded that boys receive more attention and esteem-building encouragement from teachers; that classroom activities were generally more maleoriented; and that teacher-student interactions in math class were particularly favorable toward boys. Recent research also indicates that girls report lower teacher expectation and less classroom teaching time spent on learning and activity that are perceived as relevant to the world outside of the classroom (Gentry & Owen, 2004;Green, 2002;Jussim & Harber, 2005). Even high-achieving girls are seen by teachers as being less logical, less independent in math, and liking math less than their equally achieving boy counterparts (Tiedemann, 2002).…”
Section: Individual-level Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the American Association of University Women Annual Report (1992) concluded that boys receive more attention and esteem-building encouragement from teachers; that classroom activities were generally more maleoriented; and that teacher-student interactions in math class were particularly favorable toward boys. Recent research also indicates that girls report lower teacher expectation and less classroom teaching time spent on learning and activity that are perceived as relevant to the world outside of the classroom (Gentry & Owen, 2004;Green, 2002;Jussim & Harber, 2005). Even high-achieving girls are seen by teachers as being less logical, less independent in math, and liking math less than their equally achieving boy counterparts (Tiedemann, 2002).…”
Section: Individual-level Factorsmentioning
confidence: 99%
“…Meaningful and authentic instruction provides opportunities for students to connect personal goals and interests to classroom experiences, increasing their feelings of competence and autonomy and supporting the subjective task value they attach to the course material (Gentry & Owen, 2004;Wang, 2012). Instruction that facilitates interaction and cooperation can increase students' interest and foster competence and commitment to the class (Newman & Wehlage, 1993).…”
Section: Assessing Math Classroom Climatementioning
confidence: 99%
“…Although these are different concepts, they affect each other (Gentry & Owen, 2004). For example, when a task has appropriate challenges, students may think it is appealing, or when students find meaning in the content they learn, their choices are influenced.…”
Section: Introductionmentioning
confidence: 95%
“…Students find STEM courses more meaningful when they connect classroom experiences with personal goals (Gentry & Owen, 2004). Personally relevant academic tasks enhance motivation, attention, learning, and task identification (Hidi & Harackiewicz, 2000).…”
Section: Personal Goals and Values Enhance Stem Educationmentioning
confidence: 99%